A new SNR with TeV shell-type morphology: HESS J1731-347 - Abramowski, A.; Acero, Fabio; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Becherini, Y.; Becker, J.; Behera, B.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2011)
Aims. The recent discovery of the radio shell-type supernova remnant (SNR), G353.6-0.7, in spatial coincidence with the unidentified TeV source HESS J1731-347 has motivated further observations of the source with the High Energy Stereoscopic System (HESS) Cherenkov telescope array to test a possible association of the γ-ray emission with the SNR. Methods. With a total of 59 h of observation, representing about four times the initial exposure available in the discovery paper of HESS J1731-347, the γ-ray morphology is investigated and compared with the radio morphology. An estimate of the distance is derived by comparing the interstellar absorption derived from X-rays and the one obtained from CO and HI observations. Results. The deeper γ-ray observation of the source has revealed a large shell-type structure with similar position and extension (r ∼ 0.25°) as the radio SNR, thus confirming their association. By accounting for the HESS angular resolution and projection effects within a simple shell model, the radial profile is compatible with a thin, spatially unresolved, rim. Together with RX J1713.7-3946, RX J0852.0-4622 and SN 1006, HESS J1731-347 is now the fourth SNR with a significant shell morphology at TeV energies. The derived lower limit on the distance of the SNR of 3.2 kpc is used together with radio and X-ray data to discuss the possible origin of the γ-ray emission, either via inverse Compton scattering of electrons or the decay of neutral pions resulting from proton-proton interaction. © 2011 ESO.
Keywords: Astroparticle physics; Cosmic rays; ISM: supernova remnants

A search for a dark matter annihilation signal toward the Canis major overdensity with H.E.S.S. - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, V.; Borrel, V.; Braun, Isabel V; Brion, E.; et al. (Astrophysical Journal, 2009)
A search for a dark matter (DM) annihilation signal into γ-rays toward the direction of the Canis Major (CMa) overdensity is presented. The nature of CMa is still controversial and one scenario represents it as a dwarf galaxy, making it an interesting candidate for DM annihilation searches. A total of 9.6 hr of high-quality data were collected with the H.E.S.S. array of Imaging Atmospheric Cherenkov Telescopes, and no evidence for a very high energy γ-ray signal is found. Upper limits on the CMa dwarf galaxy mass of the order of 10 M are derived at the 95% confidence level (CL) assuming neutralino masses in the range 500 GeV-10 TeV and relatively large annihilation cross sections. Constraints on the velocity-weighted annihilation cross section 〈σv〉 are calculated for specific weakly interacting massive-particle scenarios, using a Navarro-Frenk-White model for the DM halo profile and taking advantage of numerical simulations of hierarchical structure formation. Assuming a total halo mass of 3 × 10 M, 95% CL exclusion limits of the order of 5 × 10 cm s are reached in the 500 GeV-10 TeV DM particle mass interval. © 2009. The American Astronomical Society. All rights reserved..
Keywords: dark matter; galaxies: dwarf; gamma rays: observations

Constraints on the gamma-ray emission from the cluster-scale AGN outburst in the Hydra A galaxy cluster - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2012)
Context. In some galaxy clusters, powerful active galactic nuclei (AGN) have blown bubbles with cluster scale extent into the ambient medium. The main pressure support of these bubbles is not known to date, but cosmic rays are a viable possibility. For such a scenario copious gamma-ray emission is expected as a tracer of cosmic rays from these systems. Aims. Hydra A, the closest galaxy cluster hosting a cluster scale AGN outburst, located at a redshift of 0.0538, is investigated for being a gamma-ray emitter with the High Energy Stereoscopic System (H.E.S.S.) array and the Fermi Large Area Telescope (Fermi-LAT). Methods. Data obtained in 20.2 h of dedicated H.E.S.S. observations and 38 months of Fermi-LAT data, gathered by its usual all-sky scanning mode, have been analyzed to search for a gamma-ray signal. Results. No signal has been found in either data set. Upper limits on the gamma-ray flux are derived and are compared to models. These are the first limits on gamma-ray emission ever presented for galaxy clusters hosting cluster scale AGN outbursts. Conclusions. The non-detection of Hydra A in gamma-rays has important implications on the particle populations and physical conditions inside the bubbles in this system. For the case of bubbles mainly supported by hadronic cosmic rays, the most favorable scenario, which involves full mixing between cosmic rays and embedding medium, can be excluded. However, hadronic cosmic rays still remain a viable pressure support agent to sustain the bubbles against the thermal pressure of the ambient medium. The largest population of highly-energetic electrons, which are relevant for inverse-Compton gamma-ray production is found in the youngest inner lobes of Hydra A. The limit on the inverse-Compton gamma-ray flux excludes a magnetic field below half of the equipartition value of 16 μG in the inner lobes. © 2012 ESO.
Keywords: Galaxies: active; Galaxies: clusters: individual: Hydra A; Gamma rays: galaxies: clusters

Constraints on the multi-TeV particle population in the Coma galaxy cluster with HESS observations - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; Brion, E.; et al. (Astronomy & Astrophysics, 2009)
Alms. Galaxy clusters are key targets in the search for ultra high energy particle accelerators. The Coma cluster represents one of the best candidates for such a search owing to its high mass, proximity, and the established non-thermal radio emission centred on the cluster core. Methods. The HESS (High Energy Stereoscopic System) telescopes observed Coma for ∼8 h in a search for γ-ray emission at energies >1 TeV. The large 3.5° FWHM field of view of HESS is ideal for viewing a range of targets at various sizes including the Coma cluster core, the radio-relic (1253+275) and merger/infall (NGC 4839) regions to the southwest, and features greater than 1° away. Results. No evidence for point-like nor extended TeV γ-ray emission was found and upper limits to the TeV flux F(E) for E > 1, >5, and > 10 TeV were set for the Coma core and other regions. Converting these limits to an energy flux E F(E) the lowest or most constraining is the E > 5 TeV upper limit for the Coma core (0.2° radius) at ∼8% Crab flux units or ∼10 ph cm s . Conclusions. The upper limits for the Coma core were compared with a prediction for the γ-ray emission from proton-proton interactions, the level of which ultimately scales with the mass of the Coma cluster. A direct constraint using our most stringent limit for E > 5 TeV, on the total energy content in non-thermal protons with injection energy spectrum αE and spatial distribution following the thermal gas in the cluster, is found to be ∼0.2 times the thermal energy, or ∼10 erg. The E > 5 TeV γ-ray threshold in this case corresponds to cosmic- ray proton energies ≳50 TeV. Our upper limits rule out the most optimistic theoretical models for gamma ray emission from clusters and complement radio observations which constrain the cosmic ray content in clusters at significantly lower proton energies, subject to assumptions on the magnetic field strength. ©ESO 2009.
Keywords: Galaxies: Clusters: Individual: Coma (ACO 1656); Gamma rays: Observations

Detection of gamma rays from a starburst galaxy - Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, J.; et al. (Science, 2009)
Starburst galaxies exhibit in their central regions a highly increased rate of supernovae, the remnants of which are thought to accelerate energetic cosmic rays up to energies of -10 electron volts. We report the detection of gamma rays-tracers of such cosmic rays-from the starburst galaxy NGC 253 using the High Energy Stereoscopic System (H.E.S.S.) array of imaging atmospheric Cherenkov telescopes. The gamma-ray flux above 220 billion electron volts is F = (5.5 = 1.0 ± 2.8) x 10 cm s, implying a cosmic-ray density about three orders of magnitude larger than that in the center of the Milky Way. The fraction of cosmic-ray energy channeled into gamma rays in this starburst environment is five times as large as that in our Galaxy.

Detection of very high energy radiation from HESS J1908+063 confirms the Milagro unidentified source MGRO J1908+06 - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, Wystan; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Astronomy & Astrophysics, 2009)
Aims. Detection of a γ-ray source above 300 GeV is reported, confirming the unidentified source MGRO J1908+06, discovered by the Milagro collaboration at a median energy of 20 TeV. Methods. The source was observed during 27 h as part of the extension of the HESS Galactic plane survey to longitudes >30°. Results. HESS J108+063 is detected at a significance level of 10.9σ with an integral flux above 1 TeV of (3.76 ± 0.29 ph cm s, and a spectral photon index Γ = 2.10 ± 0.07 ± 0.2. The positions and fluxes of HESS J1908+063 and MGRO J1908+06 are in good agreement. Possible counterparts at other wavelengths and the origin of the γ-ray emission are discussed. The nearby unidentified GeV source, GRO J1908+0556 (GeV) which also remains unidentified and the new Fermi pulsar 0FGL J1907.5+0617, may be connected to the TeV source. © ESO 2009.
Keywords: Gamma rays; Observations

Discovery and follow-up studies of the extended, off-plane, VHE gamma-ray source HESS J1507-622 - Acero, Fabio; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, Julien; et al. (Astronomy & Astrophysics, 2010)
Context. The detection of gamma-rays in the very-high-energy (VHE) range (100 GeV-100 TeV) offers the possibility of studying the parent population of ultrarelativistic particles found in astrophysical sources, so it is useful for understanding the underlying astrophysical processes in nonthermal sources. Aims. The discovery of the VHE gamma-ray source HESS J1507-622 is reported and possibilities regarding its nature are investigated. Methods. The H.E.S.S. array of imaging atmospheric Cherenkov telescopes (IACTs) has a high sensitivity compared with previous instruments (∼1% of the Crab flux in 25 h observation time for a 5σ point-source detection) and has a large field of view (∼5° in diameter). HESS J1507-622 was discovered within the ongoing H.E.S.S. survey of the inner Galaxy, and the source was also studied by means of dedicated multiwavelength observations. Results. A Galactic gamma-ray source, HESS J1507-622, located ∼3.5° from the Galactic plane was detected with a statistical significance >9σ. Its energy spectrum is well fitted by a power law with spectral index Γ = 2.24 ± 0.16 ± 0.20 and a flux above 1 TeV of (1.5 ± 0.4 ± 0.3) × 10 cm s. Possible interpretations (considering both hadronic and leptonic models) of the VHE gamma-ray emission are discussed in the absence of an obvious counterpart. © ESO 2010.
Keywords: gamma rays: general; X-rays: general

Discovery of gamma-ray emission from the extragalactic pulsar wind nebula N 157B with H.E.S.S. - Abramowski, A.; Acero, Fabio; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2012)
We present the significant detection of the first extragalactic pulsar wind nebula (PWN) detected in gamma rays, N- 157B, located in the large Magellanic Cloud (LMC). Pulsars with high spin-down luminosity are found to power energised nebulae that emit gamma rays up to energies of several tens of TeV. N- 157B is associated with PSR- J0537-6910, which is the pulsar with the highest known spin-down luminosity. The High Energy Stereoscopic System telescope array observed this nebula on a yearly basis from 2004 to 2009 with a dead-time corrected exposure of 46- h. The gamma-ray spectrum between 600- GeV and 12- TeV is well-described by a pure power-law with a photon index of 2.8 ± 0.2 ± 0.3 and a normalisation at 1- TeV of (8.2 ± 0.8 ± 2.5 ) × 10 cm - s - TeV . A leptonic multi-wavelength model shows that an energy of about 4 × 10 erg is stored in electrons and positrons. The apparent efficiency, which is the ratio of the TeV gamma-ray luminosity to the pulsar's spin-down luminosity, 0.08% ± 0.01%, is comparable to those of PWNe found in the Milky Way. The detection of a PWN at such a large distance is possible due to the pulsar's favourable spin-down luminosity and a bright infrared photon-field serving as an inverse-Compton-scattering target for accelerated leptons. By applying a calorimetric technique to these observations, the pulsar's birth period is estimated to be shorter than 10 ms. © ESO, 201
Keywords: Gamma rays: general; ISM: supernova remnants; Magellanic Clouds; Pulsars: individual: PSR J0537-6910

Discovery of TeV γ-ray emission from PKS 0447-439 and derivation of an upper limit on its redshift - Abramowski, A.; Acero, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Behera, B.; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
Very high-energy γ-ray emission from PKS 0447-439 was detected with the H.E.S.S. Cherenkov telescope array in December 2009. This blazar is one of the brightest extragalactic objects in the Fermi bright source list and has a hard spectrum in the MeV to GeV range. In the TeV range, a photon index of 3.89 ± 0.37 (stat) ±0.22 (sys) and a flux normalisation at 1 TeV, Φ = (3.5 ± 1.1(stat) ± 0.9(sys)) × 10 cm s TeV were found. The detection with H.E.S.S. triggered observations in the X-ray band with the Swift and RXTE telescopes. Simultaneous UV and optical data from Swift UVOT and data from the optical telescopes ATOM and ROTSE are also available. The spectrum and light curve measured with H.E.S.S. are presented and compared to the multi-wavelength data at lower energies. A rapid flare is seen in the Swift XRT and RXTE data, together with a flux variation in the UV band, at a time scale of the order of one day. A firm upper limit of z < 0.59 on the redshift of PKS 0447-439 is derived from the combined Fermi-LAT and H.E.S.S. data, given the assumptions that there is no upturn in the intrinsic spectrum above the Fermi-LAT energy range and that absorption on the extragalactic background light (EBL) is not weaker than the lower limit provided by current models. The spectral energy distribution is well described by a simple one-zone synchrotron self-Compton scenario, if the redshift of the source is less than z â‰ 0.4. © 2013 ESO.
Keywords: BL Lacertae objects: individual: PKS 0447-439; Galaxies: active; Gamma rays: galaxies; Radiation mechanisms: non-thermal

Discovery of the source HESS J1356-645 associated with the young and energetic PSR J1357-6429 - van Eldik, Christopher; Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Becherini, Y.; Becker, J.; Behera, B.; et al. (Astronomy & Astrophysics, 2011)
Context. Several newly discovered very-high-energy (VHE; E > 100 GeV) γ-ray sources in the Galaxy are thought to be associated with energetic pulsars. Among them, middle-aged (10 yr) systems exhibit large centre-filled VHE nebulae, offset from the pulsar position, which result from the complex relationship between the pulsar wind and the surrounding medium, and reflect the past evolution of the pulsar. Aims. Imaging Atmospheric Cherenkov Telescopes (IACTs) have been successful in revealing extended emission from these sources in the VHE regime. Together with radio and X-ray observations, this observational window allows one to probe the energetics and magnetic field inside these large-scale nebulae. Methods. H.E.S.S., with its large field of view, angular resolution of 0.1° and unprecedented sensitivity, has been used to discover a large population of such VHE sources. In this paper, the H.E.S.S. data from the continuation of the Galactic Plane Survey (-80° < < 60°, |b| < 3°), together with the existing multi-wavelength observations, are used. Results. A new VHE γ-ray source was discovered at RA (J2000) = 135600, Dec (J2000) =-64°30′00′′ with a 2′ statistical error in each coordinate, namely HESS J1356-645. The source is extended, with an intrinsic Gaussian width of (0.20 ± 0.02)°. Its integrated energy flux between 1 and 10 TeV of 8 × 10 erg cm s represents ∼11% of the Crab Nebula flux in the same energy band. The energy spectrum between 1 and 20 TeV is well described by a power law dN/dE E with photon index Γ = 2.2 ± 0.2 ± 0.2. The inspection of archival radio images at three frequencies and the analysis of X-ray data from ROSAT/PSPC and XMM-Newton/MOS reveal the presence of faint non-thermal diffuse emission coincident with HESS J1356-645. Conclusions. HESS J1356-645 is most likely associated with the young and energetic pulsar PSR J1357-6429 (d = 2.4 kpc, τ = 7.3 kyr and Å-= 3.1 × 10 erg s), located at a projected distance of ∼5 pc from the centroid of the VHE emission. HESS J1356-645 and its radio and X-ray counterparts would thus represent the nebula resulting from the past history of the PSR J1357-6429 wind. In a simple one-zone model, © 2011 ESO.
Keywords: gamma rays: general; ISM: individual objects: HESS J1356-645; ISM: individual objects: PSR J1357-6429; surveys

Discovery of very high energy γ-ray emission from centaurus a with H.E.S.S. - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Astrophysical Journal, 2009)
We report the discovery of faint very high energy (VHE; E > 100GeV) γ-ray emission from the radio galaxy Centaurus A in observations performed with the High Energy Stereoscopic System (H.E.S.S.) experiment, an imaging atmospheric Cherenkov telescope array consisting of four telescopes located in Namibia. Centaurus A has been observed for more than 120hr. A signal with a statistical significance of 5.0σ is detected from the region including the radio core and the inner kpc jets. The integral flux above an energy threshold of 250 GeV is measured to be 0.8% of the flux of the Crab Nebula (apparent luminosity: L(>250GeV) 2.6 × 10ergs, adopting a distance of 3.8Mpc). The spectrum can be described by a power law with a photon index of 2.7 0.5 0.2. No significant flux variability is detected in the data set. However, the low flux only allows detection of variability on the timescale of days to flux increments above a factor of 15-20 (3σ and 4σ, respectively). The discovery of VHE γ-ray emission from Centaurus A reveals particle acceleration in the source to >TeV energies and, together with M87, establishes radio galaxies as a class of VHE emitters. © 2009. The American Astronomical Society. All rights reserved..
Keywords: Galaxies: active; Galaxies: individual (Cen A); Gamma rays: observations

Discovery of VHE γ-ray emission and multi-wavelength observations of the BL Lacertae object 1RXS J101015.9-311909 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; Biteau, J.; et al. (Astronomy & Astrophysics, 2012)
Keywords: gamma rays: galaxies; galaxies: active; BL Lacertae objects: individual: 1RXS J101015.9-311909

Discovery of VHE emission towards the Carina arm region with the H.E.S.S. telescope array: HESS? J1018-589 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; Biteau, J.; et al. (Astronomy & Astrophysics, 2012)
The Carina arm region, containing the supernova remnant SNR? G284.3-1.8, the high-energy (HE; E > 100 MeV) binary 1FGL? J1018.6-5856 and the energetic pulsar PSR? J1016-5857 and its nebula, has been observed with the H.E.S.S. telescope array. The observational coverage of the region in very-high-energy (VHE; E > 0.1? TeV) γ-rays benefits from deep exposure (40? h) of the neighboring open cluster Westerlund 2. The observations have revealed a new extended region of VHE γ-ray emission. The new VHE source HESS? J1018-589 shows a bright, point-like emission region positionally coincident with SNR? G284.3-1.8 and 1FGL? J1018.6-5856 and a diffuse extension towards the direction of PSR? J1016-5857. A soft (Γ = 2.7 ± 0.5) photon? index, with a differential flux at 1? TeV of N = (4.2 ± 1.1) × 10? TeV? cm? s is found for the point-like source, whereas the total emission region including the diffuse emission region is well fit by a power-law function with spectral index Γ = 2.9 ± 0.4 and differential flux at 1? TeV of N = (6.8 ± 1.6) × 10? TeV? cm? s. This H.E.S.S. detection motivated follow-up X-ray observations with the XMM-Newton satellite to investigate the origin of the VHE emission. The analysis of the XMM-Newton data resulted in the discovery of a bright, non-thermal point-like source (XMMU J101855.4-58564) with a photon index of Γ = 1.65 ± 0.08 in the center of SNR? G284.3-1.8, and a thermal, extended emission region coincident with its bright northern filament. The characteristics of this thermal emission are used to estimate the plasma density in the region as n 0.5 cm (2.9? kpc/d). The position of XMMU? J101855.4-58564 is compatible with the position reported by the Fermi-LAT collaboration for the binary system 1FGL? J1018.6-5856 and the variable Swift XRT source identified with it. The new X-ray data are used alongside archival multi-wavelength data to investigate the relationship between the VHE γ-ray emission from HESS? J1018-589 and the various potential counterparts in the Carina arm region. © ESO, 2012.
Keywords: Gamma rays: stars; ISM: individual objects: 1FGL J1018.6-5856; ISM: individual objects: PSRJ1016-5857; ISM: individual objects: SNRG284.3-1.8

Discovery of VHE γ -rays from the BL Lacertae object PKS 0548-322 - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, J.; et al. (Astronomy & Astrophysics, 2010)
Aims. PKS 0548-322 (z = 0.069) is a "high-frequency-peaked" BL Lac object and a candidate very high energy (VHE, E > 100 GeV) γ-ray emitter, due to its high X-ray and radio flux. Observations at the VHE band provide insights into the origin of very energetic particles present in this source and the radiation processes at work. Methods. We report observations made between October 2004 and January 2008 with the HESS array, a four imaging atmospheric-Cherenkov telescopes. Contemporaneous UV and X-ray observations with the Swift satellite in November 2006 are also reported. Results. PKS 0548-322 is detected for the first time in the VHE band with HESS We measure an excess of 216 γ-rays corresponding to a significance of 5.6 standard deviations. The photon spectrum of the source is described by a power-law, with a photon index of Γ = 2.86 ± 0.34 ± 0.10 . The integral flux above 200 GeV is ∼1.3% of the flux of the Crab Nebula, and is consistent with being constant in time. Contemporaneous Swift/XRT observations reveal an X-ray flux between 2 and 10 keV of F = (2.3±0.2)×10 erg cm s, an intermediate intensity state with respect to previous observations. The spectral energy distribution can be reproduced using a simple one-zone synchrotron self Compton model, with parameters similar those observed for other sources of this type. © 2010 ESO.
Keywords: BL Lacertae objects: individual: PKS 0548-322; galaxies: active; gamma rays: observations

Energy spectrum of cosmic-ray electrons at TeV energies - Aharonian, F.; Akhperjanian, A. G.; Barres De Almeida, Ulisses; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; Braun, Isabel V; et al. (Physical Review Letters, 2008)
The very large collection area of ground-based γ-ray telescopes gives them a substantial advantage over balloon or satellite based instruments in the detection of very-high-energy (>600GeV) cosmic-ray electrons. Here we present the electron spectrum derived from data taken with the High Energy Stereoscopic System (H.E.S.S.) of imaging atmospheric Cherenkov telescopes. In this measurement, the first of this type, we are able to extend the measurement of the electron spectrum beyond the range accessible to direct measurements. We find evidence for a substantial steepening in the energy spectrum above 600 GeV compared to lower energies. © 2008 The American Physical Society.

Erratum: "Search for Dark Matter Annihilation Signals from the Fornax Galaxy Cluster with H.E.S.S.'' (2012, ApJ, 750, 123) - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Barres De Almeida, U.; Becherini, Y.; Becker, J.; Behera, B.; Bernlöhr, K.; et al. (Astrophysical Journal, 2014)

First detection of VHE γ-rays from SN 1006 by HESS - Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Beilicke, M.; Bernloehr, K.; Bochow, A.; Boisson, C.; et al. (Astronomy & Astrophysics, 2010)
Aims. Recent theoretical predictions of the lowest very high energy (VHE) luminosity of SN 1006 are only a factor 5 below the previously published HESS upper limit, thus motivating further in-depth observations of this source. Methods. Deep observations at VHE energies (above 100 GeV) were carried out with the high energy stereoscopic system (HESS) of Cherenkov Telescopes from 2003 to 2008. More than 100 h of data have been collected and subjected to an improved analysis procedure. Results. Observations resulted in the detection of VHE γ-rays from SN 1006. The measured γ-ray spectrum is compatible with a power-law, the flux is of the order of 1% of that detected from the Crab Nebula, and is thus consistent with the previously established HESS upper limit. The source exhibits a bipolar morphology, which is strongly correlated with non-thermal X-rays. Conclusions. Because the thickness of the VHE-shell is compatible with emission from a thin rim, particle acceleration in shock waves is likely to be the origin of the γ-ray signal. The measured flux level can be accounted for by inverse Compton emission, but a mixed scenario that includes leptonic and hadronic components and takes into account the ambient matter density inferred from observations also leads to a satisfactory description of the multi-wavelength spectrum. © 2010 ESO.
Keywords: Gamma rays: stars; Supernovae: individual: SN 1006 (G327.6+14.6)

H.E.S.S. constraints on dark matter annihilations towards the sculptor and carina dwarf galaxies - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Barnacka, A.; Barres De Almeida, U.; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; Behera, B.; Bernlöhr, K.; et al. (Astroparticle Physics, 2011)
The Sculptor and Carina dwarf spheroidal galaxies were observed with the H.E.S.S. Cherenkov telescope array between January 2008 and December 2009. The data sets consist of a total of 11.8 h and 14.8 h of high quality data, respectively. No gamma-ray signal was detected at the nominal positions of these galaxies above 220 GeV and 320 GeV, respectively. Upper limits on the gamma-ray fluxes at 95% CL assuming two forms for the spectral energy distribution (a power law shape and one derived from dark matter annihilation) are obtained at the level of 10-10 cm s in the TeV range. Constraints on the velocity weighted dark matter particle annihilation cross section for both Sculptor and Carina dwarf galaxies range from 〈σv〉 ∼ 10 cm s down to 〈σv〉 ∼ 10 cm s depending on the dark matter halo model used. Possible enhancements of the gamma-ray flux are studied: the Sommerfeld effect, which is found to exclude some dark matter particle masses, the internal Bremsstrahlung and clumps in the dark-matter halo distributions. © 2011 Published by Elsevier B.V.
Keywords: Carina; Dark matter; Gamma-rays: observations - Dwarf spheroidal galaxy; Internal Bremsstrahlung; Sculptor; Sommerfeld enhancement

H.E.S.S. discovery of VHE γ-rays from the quasar PKS 1510-089 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Behera, B.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2013)
The quasar PKS 1510-089 (z = 0.361) was observed with the H.E.S.S. array of imaging atmospheric Cherenkov telescopes during high states in the optical and GeV bands, to search for very high energy (VHE, defined as E ≥ 0.1 TeV) emission. VHE γ-rays were detected with a statistical significance of 9.2 standard deviations in 15.8 h of H.E.S.S. data taken during March and April 2009. A VHE integral flux of I(0.15 TeV < E < 1.0TeV) = (1.0 ±0.2 ±0.2) ×10 cm s is measured. The best-fit power law to the VHE data has a photon index of γ = 5.4 ± 0.7 ± 0.3. The GeV and optical light curves show pronounced variability during the period of H.E.S.S. observations. However, there is insufficient evidence to claim statistically significant variability in the VHE data. Because of its relatively high redshift, the VHE flux from PKS 1510-089 should suffer considerable attenuation in the intergalactic space due to the extragalactic background light (EBL). Hence, the measured γ-ray spectrum is used to derive upper limits on the opacity due to EBL, which are found to be comparable with the previously derived limits from relatively-nearby BL Lac objects. Unlike typical VHE-detected blazars where the broadband spectrum is dominated by nonthermal radiation at all wavelengths, the quasar PKS 1510-089 has a bright thermal component in the optical to UV frequency band. Among all VHE detected blazars, PKS 1510-089 has the most luminous broad line region. The detection of VHE emission from this quasar indicates a low level of γ - γ absorption on the internal optical to UV photon field. © 2013 ESO.
Keywords: Gamma rays: galaxies; Infrared: diffuse background; Quasars: individual: PKS 1510; 089

HESS J1943+213: A candidate extreme BL Lacertae object - van Eldik, Christopher; Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; et al. (Astronomy & Astrophysics, 2011)
Context. The H.E.S.S. Cherenkov telescope array has been surveying the Galactic plane for new VHE (>100 GeV) gamma-ray sources. Aims. We report on a newly detected point-like source, HESS J1943+213. This source coincides with an unidentified hard X-ray source IGR J19443+2117, which was proposed to have radio and infrared counterparts. Methods. We combine new H.E.S.S., Fermi/LAT and Nançay Radio Telescope observations with pre-existing non-simultaneous multi-wavelength observations of IGR J19443+2117 and discuss the likely source associations as well as the interpretation as an active galactic nucleus, a gamma-ray binary or a pulsar wind nebula. Results. HESS J1943+213 is detected at the significance level of 7.9σ (post-trials) at RA(J2000)= 19 4355 ± 1 ± 1 , Dec(J2000)= +21° 18'8" ± 17" ± 20". The source has a soft spectrum with photon index Γ = 3.1 ± 0.3 ± 0.2 and a flux above 470 GeV of (1.3 ± 0.2 ± 0.3) × 10 cm s . There is no Fermi/LAT counterpart down to a flux limit of 6 × 10 cm s in the 0.1-100 GeV energy range (95% confidence upper limit calculated for an assumed power-law model with a photon index Γ = 2.0). The data from radio to VHE gamma-rays do not show any significant variability. Conclusions. The lack of a massive stellar counterpart disfavors the binary hypothesis, while the soft VHE spectrum would be very unusual in case of a pulsar wind nebula. In addition, the distance estimates for Galactic counterparts places them outside of the Milky Way. All available observations favor an interpretation as an extreme, high-frequency peaked BL Lac object with a redshift z > 0.14. This would be the first time a blazar is detected serendipitously from ground-based VHE observations, and the first VHE AGN detected in the Galactic Plane. © 2011 ESO.
Keywords: BL Lacertae objects: individual: IGR J19443+2117; galaxies: active; gamma rays: general

H.E.S.S. observations of the binary system PSR B1259-63/LS 2883 around the 2010/2011 periastron passage - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
Aims. We present very high energy (VHE; E > 100 GeV) data from the γ-ray binary system PSR B1259-63/LS 2883 taken around its periastron passage on 15th of December 2010 with the High Energy Stereoscopic System (H.E.S.S.) of Cherenkov Telescopes. We aim to search for a possible TeV counterpart of the GeV flare detected by the Fermi LAT. In addition, we aim to study the current periastron passage in the context of previous observations taken at similar orbital phases, testing the repetitive behaviour of the source. Methods. Observations at VHEs were conducted with H.E.S.S. from 9th to 16th of January 2011. The total dataset amounts to 6 h of observing time. The data taken around the 2004 periastron passage were also re-analysed with the current analysis techniques in order to extend the energy spectrum above 3 TeV to fully compare observation results from 2004 and 2011. Results. The source is detected in the 2011 data at a significance level of 11.5σ revealing an averaged integral flux above 1 TeV of (1.01 ± 0.18 ± 0.20) × 10 cm s. The differential energy spectrum follows a power-law shape with a spectral index Γ = 2.92 ± 0.30 ± 0.20 and a flux normalisation at 1 TeV of N = (1.95 ± 0.32 ± 0.39) × 10 TeV cm s. The measured light curve does not show any evidence for variability of the source on the daily scale. The re-analysis of the 2004 data yields results compatible with the published ones. The differential energy spectrum measured up to 10 TeV is consistent with a power law with a spectral index Γ = 2.81 ± 0.10 ± 0.20 and a flux normalisation at 1 TeV of N = (1.29 ± 0.08 ± 0.26) × 10 TeV cm s. Conclusions. The measured integral flux and the spectral shape of the 2011 data are compatible with the results obtained around previous periastron passages. The absence of variability in the H.E.S.S. data indicates that the GeV flare observed by Fermi LAT in the time period covered also by H.E.S.S. observations originates in a different physical scenario than the TeV emission. Moreover, the comparison of the new results to the results from the 2004 observations made at a similar orbital phase provides a stronger evidence of the repetitive behaviour of the source. © ESO, 2013.
Keywords: Gamma rays: general; Pulsars: individual: PSR B1259-63; Stars: individual: LS 2883; X-rays: binaries

HESS observations of the Carina nebula and its enigmatic colliding wind binary Eta Carinae - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; Biteau, J.; et al. (Monthly Notices of the Royal Astronomical Society, 2012)
The massive binary system Eta Carinae and the surrounding Hii complex, the Carina nebula, are potential particle acceleration sites from which very high energy (VHE; E≥ 100GeV) γ-ray emission could be expected. This paper presents data collected during VHE γ-ray observations with the HESS telescope array from 2004 to 2010, which cover a full orbit of Eta Carinae. In the 33.1-h data set no hint of significant γ-ray emission from Eta Carinae has been found and an upper limit on the γ-ray flux of (99per cent confidence level) is derived above the energy threshold of 470GeV. Together with the detection of high energy (HE; 0.1 ≤E≤ 100GeV) γ-ray emission by the Fermi Large Area Telescope up to 100GeV, and assuming a continuation of the average HE spectral index into the VHE domain, these results imply a cut-off in the γ-ray spectrum between the HE and VHE γ-ray range. This could be caused either by a cut-off in the accelerated particle distribution or by severe γ-γ absorption losses in the wind collision region. Furthermore, the search for extended γ-ray emission from the Carina nebula resulted in an upper limit on the γ-ray flux of (99per cent confidence level). The derived upper limit of ∼23 on the cosmic ray enhancement factor is compared with results found for the old-age mixed-morphology supernova remnant W28. © 2012 The Authors Monthly Notices of the Royal Astronomical Society © 2012 RAS.
Keywords: Acceleration of particles; ISM: individual objects: Carina nebula; ISM: individual objects: Eta Carina; Open clusters and associations: general; Radiation mechanisms: non-thermal; X-rays: binaries

H.E.S.S. observations of the globular clusters NGC 6388 and M15 and search for a dark matter signal - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; Behera, B.; et al. (Astrophysical Journal, 2011)
Observations of the globular clusters (GCs) NGC 6388 and M15 were carried out by the High Energy Stereoscopic System array of Cherenkov telescopes for a live time of 27.2 and 15.2 hr, respectively. No gamma-ray signal is found at the nominal target position of NGC 6388 and M15. In the primordial formation scenario, GCs are formed in a dark matter (DM) halo and DM could still be present in the baryon-dominated environment of GCs. This opens the possibility of observing a DM self-annihilation signal. The DM content of the GCs NGC 6388 and M15 is modeled taking into account the astrophysical processes that can be expected to influence the DM distribution during the evolution of the GC: the adiabatic contraction of DM by baryons, the adiabatic growth of a black hole in the DM halo, and the kinetic heating of DM by stars. Ninety-five percent confidence level exclusion limits on the DM particle velocity-weighted annihilation cross section are derived for these DM halos. In the TeV range, the limits on the velocity-weighted annihilation cross section are derived at the 10 cm s level and a few 10 cm s for NGC 6388 and M15, respectively. © 2011. The American Astronomical Society. All rights reserved..
Keywords: black hole physics; dark matter; gamma rays: general; globular clusters: individual (NGC 6388; M15)

HESS upper limit on the very high energy γ-ray emission from the globular cluster 47 Tucanae - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2009)
Observations of the globular cluster 47 Tucanae (NGC 104), which contains at least 23 ms pulsars, were performed with the HESS telescope system. The observations lead to an upper limit of F(E < 800 GeV) < 6.7 × 10-13 cm-2 s-1 on the integral γ-ray photon flux from 47 Tucanae. Considering millisecond pulsars as the unique potential source of γ-rays in the globular cluster, constraints based on emission models are derived: on the magnetic field in the average pulsar nebula and on the conversion efficiency of spin-down power to γ-ray photons or to relativistic leptons. © 2009 ESO.
Keywords: Galaxy: globular clusters: individual: 47 Tucanae; Gamma rays: observations; Stars: pulsars: general

Hess upper limits on very high energy gamma-ray emission from the microquasar grs 1915+105 - Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, Julien; et al. (Astronomy & Astrophysics, 2009)
Context: High energy particles reside in the relativistic jets of microquasars, making them possible sources of very high energy radiation (VHE, < 100 GeV). Detecting this emission would provide a new handle on jet physics. Aims: Observations of the microquasar GRS 1915+105 with the HESS telescope array were undertaken in 2004-2008 to search for VHE emission. Methods: Stereoscopic imaging of Cherenkov radiation from extensive air showers is used to reconstruct the energy and direction of the incident gamma rays. Results: There is no evidence for a VHE gamma-ray signal either from the direction of the microquasar or its vicinity. An upper limit of 6.1 × 10ph cms (99.9% confidence level) is set on the photon flux above 410 GeV, equivalent to a VHE luminosity of ̃ 10erg s at 11 kpc. Conclusions. The VHE to X-ray luminosity ratio in GRS 1915+105 is at least four orders of magnitude lower than the ratio observed in gamma-ray binaries. The VHE radiative efficiency of the compact jet is less than 0.01% based on its estimated total power of 10 erg s. Particle acceleration in GRS 1915+105 is not efficient at high energies and/or the magnetic field is too strong. It is also possible that VHE gamma-rays are produced by GRS 1915+105, but the emission is highly time-dependent. © 2009 ESO.
Keywords: Gamma rays: observations; X-rays: binaries; X-rays: individuals: GRS 1915+105

Identification of HESS J1303-631 as a pulsar wind nebula through γ -ray, X-ray, and radio observations - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2012)
Aims. The previously unidentified very high-energy (VHE; E > 100 GeV) γ-ray source HESS J1303-631, discovered in 2004, is re-examined including new data from the H.E.S.S. Cherenkov telescope array in order to identify this object. Archival data from the XMM-Newton X-ray satellite and from the PMN radio survey are also examined. Methods. Detailed morphological and spectral studies of VHE γ-ray emission as well as of the XMM-Newton X-ray data are performed. Radio data from the PMN survey are used as well to construct a leptonic model of the source. The γ-ray and X-ray spectra and radio upper limit are used to construct a one zone leptonic model of the spectral energy distribution (SED). Results. Significant energy-dependent morphology of the γ-ray source is detected with high-energy emission (E > 10 TeV) positionally coincident with the pulsar PSR J1301-6305 and lower energy emission (E < 2 TeV) extending ∼0.4° to the southeast of the pulsar. The spectrum of the VHE source can be described with a power-law with an exponential cut-off N = (5.6 ± 0.5) × 10 ± TeV ± cm ± s, Γ = 1.5 ± 0.2) and E = (7.7 ± ± ± 2.2) TeV. The pulsar wind nebula (PWN) is also detected in X-rays, extending ∼2-3′ from the pulsar position towards the center of the γ-ray emission region. A potential radio counterpart from the PMN survey is also discussed, showing a hint for a counterpart at the edge of the X-ray PWN trail and is taken as an upper limit in the SED. The extended X-ray PWN has an unabsorbed flux of F ∼ 1.6 × 10 erg cm and is detected at a significance of 6.5σ. The SED is well described by a one zone leptonic scenario which, with its associated caveats, predicts a very low average magnetic field for this source. Conclusions. Significant energy-dependent morphology of this source, as well as the identification of an associated X-ray PWN from XMM-Newton observations enable identification of the VHE source as an evolved PWN associated to the pulsar PSR J1301-6305. This identification is supported by the one zone leptonic model, which suggests that the energetics of the γ-ray and X-ray radiation are such that they may have a similar origin in the pulsar nebula. However, the large discrepancy in emission region sizes and the low level of synchrotron radiation suggest a multi-population leptonic nature. The low implied magnetic field suggests that the PWN has undergone significant expansion. This would explain the low level of synchrotron radiation and the difficulty in detecting counterparts at lower energies, the reason this source was originally classified as a "dark" VHE γ-ray source. © ESO, 2012.
Keywords: Gamma rays: general; ISM: individual objects: HESS J1303-631; Pulsars: individual: PSR J1301-6305

Limits on an energy dependence of the speed of light from a flare of the active galaxy PKS 2155-304 - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Beilicke, M.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Physical Review Letters, 2008)
In the past few decades, several models have predicted an energy dependence of the speed of light in the context of quantum gravity. For cosmological sources such as active galaxies, this minuscule effect can add up to measurable photon-energy dependent time lags. In this Letter a search for such time lags during the High Energy Stereoscopic System observations of the exceptional very high energy flare of the active galaxy PKS 2155-304 on 28 July 2006 is presented. Since no significant time lag is found, lower limits on the energy scale of speed of light modifications are derived. © 2008 The American Physical Society.

Localizing the VHE γ-ray source at the galactic centre - Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, J.; et al. (Monthly Notices of the Royal Astronomical Society, 2010)
The inner 10 pc of our Galaxy contains many counterpart candidates of the very high energy (VHE; >100 GeV) γ-ray point source HESS J1745-290. Within the point spread function of the H.E.S.S. measurement, at least three objects are capable of accelerating particles to VHE and beyond and of providing the observed γ-ray flux. Previous attempts to address this source confusion were hampered by the fact that the projected distances between these objects were of the order of the error circle radius of the emission centroid (34 arcsec, dominated by the pointing uncertainty of the H.E.S.S. instrument). Here we present H.E.S.S. data of the Galactic Centre region, recorded with an improved control of the instrument pointing compared to H.E.S.S. standard pointing procedures. Stars observed during γ-ray observations by optical guiding cameras mounted on each H.E.S.S. telescope are used for off-line pointing calibration, thereby decreasing the systematic pointing uncertainties from 20 to 6 arcsec per axis. The position of HESS J1745-290 is obtained by fitting a multi-Gaussian profile to the background-subtracted γ-ray count map. A spatial comparison of the best-fitting position of HESS J1745-290 with the position and morphology of candidate counterparts is performed. The position is, within a total error circle radius of 13 arcsec, coincident with the position of the supermassive black hole Sgr A* and the recently discovered pulsar wind nebula candidate G359.95-0.04. It is significantly displaced from the centroid of the supernova remnant Sgr A East, excluding this object with high probability as the dominant source of the VHE γ-ray emission. © 2009 The Authors. Journal compilation © 2009 RAS.
Keywords: Galaxy: centre; Gamma-rays: observations; ISM: individual: G 359.95-0.04; ISM: individual: Sgr A East; ISM: individual: Sgr A*

Measurement of the extragalactic background light imprint on the spectra of the brightest blazars observed with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
The extragalactic background light (EBL) is the diffuse radiation with the second highest energy density in the Universe after the cosmic microwave background. The aim of this study is the measurement of the imprint of the EBL opacity to γ-rays on the spectra of the brightest extragalactic sources detected with the High Energy Stereoscopic System (H.E.S.S.). The originality of the method lies in the joint fit of the EBL optical depth and of the intrinsic spectra of the sources, assuming intrinsic smoothness. Analysis of a total of ∼10γ-ray events enables the detection of an EBL signature at the 8.8σ level and constitutes the first measurement of the EBL optical depth using very-high energy (E > 100 GeV) γ-rays. The EBL flux density is constrained over almost two decades of wavelengths [0.30 μm, 17 μm] and the peak value at 1.4 μm is derived as λF = 15 ± 2 ± 3 nW m sr. © 2013 ESO.
Keywords: BL Lacertae objects: general; Cosmic background radiation; Gamma rays: galaxies

Multi-wavelength observations of H 2356-309 - van Eldik, Christopher; Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2010)
Aims. The properties of the broad-band emission from the high-frequency peaked BL Lac H 2356-309 (z = 0.165) are investigated. Methods. Very high energy (VHE; E > 100 GeV) observations of H 2356-309 were performed with the High Energy Stereoscopic System (HESS) from 2004 through 2007. Simultaneous optical/UV and X-ray observations were made with the XMM-Newton satellite on June 12/13 and June 14/15, 2005. NRT radio observations were also contemporaneously performed in 2005. ATOM optical monitoring observations were also made in 2007. Results. A strong VHE signal, ∼13σ total, was detected by HESS after the four years HESS observations (116.8 h live time). The integral flux above 240 GeV is I(>240 GeV) = (3.06 ± 0.26 ± 0.61) × 10 cm s, corresponding to ∼1.6% of the flux observed from the Crab Nebula. A time-averaged energy spectrum is measured from 200 GeV to 2 TeV and is characterized by a power law (photon index of Γ = 3.06 ± 0.15 ± 0.10). Significant small-amplitude variations in the VHE flux from H 2356-309 are seen on time scales of months and years, but not on shorter time scales. No evidence for any variations in the VHE spectral slope are found within these data. The XMM-Newton X-ray measurements show a historically low X-ray state, characterized by a hard, broken-power-law spectrum on both nights. Conclusions. The broad-band spectral energy distribution (SED) of the blazar can be adequately fit using a simple one-zone synchrotron self-Compton (SSC) model. In the SSC scenario, higher VHE fluxes could be expected in the future since the observed X-ray flux is at a historically low level. © 2010 ESO.
Keywords: BL Lacertae objects: individual: H 2356-309; Galaxies: active; Gamma rays: galaxies

PKS2005-489 at VHE: Four years of monitoring with HESS and simultaneous multi-wavelength observations - Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Bochow, A.; Boisson, C.; et al. (Astronomy & Astrophysics, 2010)
Aims: Our aim is to study the very high energy (VHE; E > 100 GeV) Γ-ray emission from BL Lac objects and the evolution in time of their broad-band spectral energy distribution (SED). Methods: VHE observations of the high-frequency peaked BL Lac object PKS 2005-489 were made with the High Energy Stereoscopic System (HESS) from 2004 through 2007. Three simultaneous multi-wavelength campaigns at lower energies were performed during the HESS data taking, consisting of several individual pointings with the XMM-Newton and RXTE satellites. Results: A strong VHE signal, ∼17ρ total, from PKS 2005-489 was detected during the four years of HESS observations (90.3 h live time). The integral flux above the average analysis threshold of 400 GeV is ∼3% of the flux observed from the Crab Nebula and varies weakly on time scales from days to years. The average VHE spectrum measured from ∼300 GeV to ∼5 TeV is characterized by a power law with a photon index, Γ = 3.20 ± 0.16 ± 0.10 At X-ray energies the flux is observed to vary by more than an order of magnitude between 2004 and 2005. Strong changes in the X-ray spectrum (ΔΓ ≈ 0.7) are also observed, which appear to be mirrored in the VHE band. Conclusions: The SED of PKS 2005-4 constructed for the first time with contemporaneous data on both humps, shows significant evolution. The large flux variations in the X-ray band, coupled with weak or no variations in the VHE band and a similar spectral behavior, suggest the emergence of a new, separate, harder emission component in September 2005. © 2010 ESO.
Keywords: BL Lacertae objects: individual: PKS 2005-489; Galaxies: active; Gamma rays: galaxies; X-rays: individuals: PKS 2005-489

Probing the ATIC peak in the cosmic-ray electron spectrum with H.E.S.S. - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, Julien; Borrel, V.; et al. (Astronomy & Astrophysics, 2009)
The measurement of an excess in the cosmic-ray electron spectrum between 300 and 800 GeV by the ATIC experiment has - together with the PAMELA detection of a rise in the positron fraction up to ≈100 GeV - motivated many interpretations in terms of dark matter scenarios; alternative explanations assume a nearby electron source like a pulsar or supernova remnant. Here we present a measurement of the cosmic-ray electron spectrum with H.E.S.S. starting at 340 GeV. While the overall electron flux measured by H.E.S.S. is consistent with the ATIC data within statistical and systematic errors, the H.E.S.S. data exclude a pronounced peak in the electron spectrum as suggested for interpretation by ATIC. The H.E.S.S. data follow a power-law spectrum with spectral index of 3.0 ±0.1(stat.) ±0.3(syst.), which steepens at about 1 TeV. © ESO 2009.
Keywords: Cosmic rays; Methods: data analysis

Revisiting the Westerlund 2 field with the HESS telescope array - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Barnacka, A.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; Behera, B.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2011)
Aims. Previous observations with the HESS telescope array revealed the existence of extended very-high-energy (VHE; E > 100 GeV) γ-ray emission, HESS J1023-575, coincident with the young stellar cluster Westerlund 2. At the time of discovery, the origin of the observed emission was not unambiguously identified, and follow-up observations have been performed to further investigate the nature of this γ-ray source. Methods. The Carina region towards the open cluster Westerlund 2 has been re-observed, increasing the total exposure to 45.9 h. The combined dataset includes 33 h of new data and now permits a search for energy-dependent morphology and detailed spectroscopy. Results. A new, hard spectrum VHE γ-ray source, HESS J1026-582, was discovered with a statistical significance of 7σ. It is positionally coincident with the Fermi LAT pulsar PSR J1028-5819. The positional coincidence and radio/γ-ray characteristics of the LAT pulsar favors a scenario where the TeV emission originates from a pulsar wind nebula. The nature of HESS J1023-575 is discussed in light of the deep HESS observations and recent multi-wavelength discoveries, including the Fermi LAT pulsar PSR J1022-5746 and giant molecular clouds in the region. Despite the improved VHE dataset, a clear identification of the object responsible for the VHE emission from HESS J1023-575 is not yet possible, and contribution from the nearby high-energy pulsar and/or the open cluster remains a possibility. © 2010 ESO.
Keywords: gamma rays: stars; HII regions

Search for a dark matter annihilation signal from the galactic center halo with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Barnacka, A.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; Behera, B.; Bernloehr, K.; et al. (Physical Review Letters, 2011)
A search for a very-high-energy (VHE; 100GeV) γ-ray signal from self-annihilating particle dark matter (DM) is performed towards a region of projected distance r∼45-150pc from the Galactic center. The background-subtracted γ-ray spectrum measured with the High Energy Stereoscopic System (H.E.S.S.) γ-ray instrument in the energy range between 300-GeV and 30-TeV shows no hint of a residual γ-ray flux. Assuming conventional Navarro-Frenk-White and Einasto density profiles, limits are derived on the velocity-weighted annihilation cross section σv as a function of the DM particle mass. These are among the best reported so far for this energy range and in particular differ only little between the chosen density profile parametrizations. In particular, for the DM particle mass of ∼1TeV, values for σ above 3×1025cm3s1 are excluded for the Einasto density profile. © 2011 American Physical Society.

Search for dark matter annihilation signals from the Fornax galaxy cluster with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Becherini, Y.; Becker, J.; Behera, B.; Bernloehr, K.; et al. (Astrophysical Journal, 2012)
The Fornax galaxy cluster was observed with the High Energy Stereoscopic System for a total live time of 14.5hr, searching for very high energy (VHE; E > 100GeV) γ-rays from dark matter (DM) annihilation. No significant signal was found in searches for point-like and extended emissions. Using several models of the DM density distribution, upper limits on the DM velocity-weighted annihilation cross-section 〈σv〉 as a function of the DM particle mass are derived. Constraints are derived for different DM particle models, such as those arising from Kaluza-Klein and supersymmetric models. Various annihilation final states are considered. Possible enhancements of the DM annihilation γ-ray flux, due to DM substructures of the DM host halo, or from the Sommerfeld effect, are studied. Additional γ-ray contributions from internal bremsstrahlung and inverse Compton radiation are also discussed. For a DM particle mass of 1TeV, the exclusion limits at 95% of confidence level reach values of 〈σv〉 10 cm s, depending on the DM particle model and halo properties. Additional contribution from DM substructures can improve the upper limits on 〈σv〉 by more than two orders of magnitude. At masses around 4.5TeV, the enhancement by substructures and the Sommerfeld resonance effect results in a velocity-weighted annihilation cross-section upper limit at the level of 〈σv〉 10 cm s. © 2012. The American Astronomical Society. All rights reserved.

Search for photon-linelike signatures from dark matter annihilations with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Physical Review Letters, 2013)
Gamma-ray line signatures can be expected in the very-high-energy (E >100 GeV) domain due to self-annihilation or decay of dark matter (DM) particles in space. Such a signal would be readily distinguishable from astrophysical γ-ray sources that in most cases produce continuous spectra that span over several orders of magnitude in energy. Using data collected with the H.E.S.S. γ-ray instrument, upper limits on linelike emission are obtained in the energy range between ∼500 GeV and ∼25 TeV for the central part of the Milky Way halo and for extragalactic observations, complementing recent limits obtained with the Fermi-LAT instrument at lower energies. No statistically significant signal could be found. For monochromatic γ-ray line emission, flux limits of (2×107- 2×105) m2 s1 sr1 and (1×108-2×106) m2 s1 sr1 are obtained for the central part of the Milky Way halo and extragalactic observations, respectively. For a DM particle mass of 1 TeV, limits on the velocity-averaged DM annihilation cross section âŸ̈σvâŸ© reach ∼1027 cm3 s 1, based on the Einasto parametrization of the Galactic DM halo density profile. © 2013 American Physical Society.

Search for very-high-energy γ-ray emission from Galactic globular clusters with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
Context. Globular clusters (GCs) are established emitters of high-energy (HE, 100 MeV < E < 100 GeV) γ-ray radiation which could originate from the cumulative emission of the numerous millisecond pulsars (msPSRs) in the clusters' cores or from inverse Compton (IC) scattering of relativistic leptons accelerated in the GC environment. These stellar clusters could also constitute a new class of sources in the very-high-energy (VHE, E > 100 GeV) γ-ray regime, judging from the recent detection of a signal from the direction of Terzan 5 with the H.E.S.S. telescope array. Aims. To search for VHE γ-ray sources associated with other GCs, and to put constraints on leptonic emission models, we systematically analyzed the observations towards 15 GCs taken with the H.E.S.S. array of imaging atmospheric Cherenkov telescopes. Methods. We searched for point-like and extended VHE γ-ray emission from each GC in our sample and also performed a stacking analysis combining the data from all GCs to investigate the hypothesis of a population of faint emitters. Assuming IC emission as the origin of the VHE γ-ray signal from the direction of Terzan 5, we calculated the expected γ-ray flux from each of the 15 GCs, based on their number of millisecond pulsars, their optical brightness and the energy density of background photon fields. Results. We did not detect significant VHE γ-ray emission from any of the 15 GCs in either of the two analyses. Given the uncertainties related to the parameter determinations, the obtained flux upper limits allow to rule out the simple IC/msPSR scaling model for NGC 6388 and NGC 7078. The upper limits derived from the stacking analyses are factors between 2 and 50 below the flux predicted by the simple leptonic scaling model, depending on the assumed source extent and the dominant target photon fields. Therefore, Terzan 5 still remains exceptional among all GCs, as the VHE γ-ray emission either arises from extra-ordinarily efficient leptonic processes, or from a recent catastrophic event, or is even unrelated to the GC itself. © 2013 ESO.
Keywords: Gamma rays: general; Globular clusters: general; Pulsars: general; Radiation mechanisms: non-thermal

Simultaneous HESS and Chandra observations of Sagitarius A during an X-ray flare - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2008)
The rapidly varying ( 10 min timescale) non-thermal X-ray emission observed from Sgr A implies that particle acceleration is occuring close to the event horizon of the supermassive black hole. The TeV γ-ray source HESSJ1745-290 is coincident with Sgr A* and may be closely related to its X-ray emission. Simultaneous X-ray and TeV observations are required to elucidate the relationship between these objects. We report on joint HESS/Chandra observations performed in July 2005, during which an X-ray flare was detected. Despite a factor of ≈9 increase in the X-ray flux of Sgr A*, no evidence is found for an increase in the TeV γ-ray flux from this region. We find that an increase in the γ-ray flux of a factor of 2 or greater can be excluded at a confidence level of 99%. This finding disfavours scenarios in which the keV and TeV emission are associated with the same population of accelerated particles and in which the bulk of the γ-ray emission is produced within ∼ cm (∼100 Rs) of the supermassive black hole. © 2008 ESO.
Keywords: Gamma rays: observations; X-rays: individuals: Sgr A

Simultaneous multiwavelength observations of the second exceptional γ-ray flare of PKS 2155-304 in July 2006 - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Astronomy & Astrophysics, 2009)
Keywords: galaxies: active; galaxies: BL Lacertae objects: individual: PKS 2155-304; gamma rays: observations; X-rays: galaxies

Simultaneous observations of pks 2155-304 with hess, fermi, rxte, and atom: Spectral energy distributions and variability in a low state - van Eldik, Christopher; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Astrophysical Journal, 2009)
We report on the first simultaneous observations that cover the optical, X-ray, and high-energy gamma-ray bands of the BL Lac object PKS2155-304. The gamma-ray bands were observed for 11 days, between 2008 August 25 and 2008 September 6 (MJD 54704-54715), jointly with the Fermi Gamma-ray Space Telescope and the HESS atmospheric Cherenkov array, providing the first simultaneous MeV-TeV spectral energy distribution (SED) with the new generation of γ-ray telescopes. The ATOM telescope and the RXTE and Swift observatories provided optical and X-ray coverage of the low-energy component over the same time period. The object was close to the lowest archival X-ray and very high energy (VHE; >100 GeV) state, whereas the optical flux was much higher. The light curves show relatively little (30%) variability overall when compared to past flaring episodes, but we find a clear optical/VHE correlation and evidence for a correlation of the X-rays with the high-energy spectral index. Contrary to previous observations in the flaring state, we do not find any correlation between the X-ray and VHE components. Although synchrotron self-Compton models are often invoked to explain the SEDs of BL Lac objects, the most common versions of these models are at odds with the correlated variability we find in the various bands for PKS2155-304. © 2009. The American Astronomical Society. All rights reserved.
Keywords: BL Lacertae objects: individual (PKS 2155-304); Galaxies: active; Gamma rays: observations

Spectral analysis and interpretation of the γ-ray emission from the starburst galaxy NGC253 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; Biteau, J.; et al. (Astrophysical Journal, 2012)
Very high energy (VHE; E ≥ 100 GeV) and high-energy (HE; 100 MeV ≤ E ≤ 100 GeV) data from γ-ray observations performed with the H.E.S.S. telescope array and the Fermi-LAT instrument, respectively, are analyzed in order to investigate the non-thermal processes in the starburst galaxy NGC253. The VHE γ-ray data can be described by a power law in energy with differential photon index Γ = 2.14 ± 0.18 ± 0.30 and differential flux normalization at 1TeV of F = (9.6 ± 1.5(+ 5.7, -2.9)) × 10 TeV cm s. A power-law fit to the differential HE γ-ray spectrum reveals a photon index of Γ = 2.24 ± 0.14 ± 0.03 and an integral flux between 200MeV and 200GeV of F(0.2-200 GeV) = (4.9 ± 1.0 ± 0.3) × 10 cm s. No evidence for a spectral break or turnover is found over the dynamic range of both the LAT instrument and the H.E.S.S. experiment: a combined fit of a power law to the HE and VHE γ-ray data results in a differential photon index Γ = 2.34 ± 0.03 with a p-value of 30%. The γ-ray observations indicate that at least about 20% of the energy of the cosmic rays (CRs) capable of producing hadronic interactions is channeled into pion production. The smooth alignment between the spectra in the HE and VHE γ-ray domain suggests that the same transport processes dominate in the entire energy range. Advection is most likely responsible for charged particle removal from the starburst nucleus from GeV to multiple TeV energies. In a hadronic scenario for the γ-ray production, the single overall power-law spectrum observed would therefore correspond to the mean energy spectrum produced by the ensemble of CR sources in the starburst region. © 2012. The American Astronomical Society. All rights reserved.
Keywords: convection; diffusion; galaxies: individual (NGC 253); galaxies: starburst; gamma rays: galaxies; radiation mechanisms: non-thermal

Spectrum and variability of the Galactic center VHE γ-ray source HESS J1745-290 - van Eldik, Christopher; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Astronomy & Astrophysics, 2009)
Aims. A detailed study of the spectrum and variability of the source HESS J1745-290 in the Galactic Center (GC) region using new data from the H.E.S.S. array of Cherenkov telescopes is presented. Flaring activity and quasi periodic oscillations (QPO) of HESS J1745-290 are investigated. Methods. The image analysis is performed with a combination of a semi-analytical shower model and the statistical moment-based Hillas technique. The spectrum and lightcurves of HESS J1745-290 are derived with a likelihood method based on a spectral shape hypothesis. Rayleigh tests and Fourier analysis of the H.E.S.S. GC signal are used to study the periodicity of the source. Results. With a three-fold increase in statistics compared to previous work, a deviation from a simple power law spectrum is detected for the first time. The measured energy spectrum over the three years 2004, 2005 and 2006 of data taking is compatible with both a power law spectrum with an exponential cut-off and a broken power law spectrum. The curvature of the energy spectrum is likely to be intrinsic to the photon source, as opposed to effects of interstellar absorption. The power law spectrum with an exponential cut-off is characterized by a photon index of 2.10 ± 0.04 ± 0.10 and a cut-off energy at 15.7 ± 3.4±2.5 TeV. The broken power law spectrum exhibits spectral indices of 2.02 ± 0.08 ± 0.10 and 2.63 ± 0.14 ± 0.10 with a break energy at 2.57 ± 0.19stat ± 0.44 TeV. No significant flux variation is found. Increases in the γ-ray flux of HESS J1745-290 by at least a factor of two would be required for a 3cr detection of a flare with time scales of an hour. Investigation of possible QPO activity at periods claimed to be detected in X-rays does not show any periodicities in the H.E.S.S. signal. © ESO 2009.
Keywords: Galaxy: center; gamma rays: observations; methods: data analysis

Very high energy gamma-ray observations of the galaxy clusters Abell 496 and Abell 85 with HESS - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2009)
Aims. The nearby galaxy clusters Abell 496 and Abell 85 are studied in the very high-energy (VHE, 100]]> GeV) band to investigate VHE cosmic rays (CRs) in this class of objects which are the largest gravitationally bound systems in the Universe.Methods. HESS, an array of four imaging atmospheric cherenkov telescopes (IACT), was used to observe the targets in the range of VHE gamma rays.Results. No significant gamma-ray signal is found at the respective position of the two clusters with several different source size assumptions for each target. In particular, emission regions corresponding to the high-density core, to the extension of the entire X-ray emission in these clusters, and to the very extended region where the accretion shock is expected are investigated. Upper limits are derived for the gamma-ray flux at energies 570]]> GeV for Abell 496 and 460]]> GeV for Abell 85.Conclusions. From the non-detection in VHE gamma rays, upper limits on the total energy of hadronic CRs in the clusters are calculated. If the cosmic-ray energy density follows the large-scale gas density profile, the limit on the fraction of energy in these non-thermal particles with respect to the total thermal energy of the intra-cluster medium (ICM) is 51% for Abell 496 and only 8% for Abell 85 due to its higher mass and higher gas density. These upper limits are compared with theoretical estimates. They predict about ∼10% of the thermal energy of the ICM in non-thermal particles. The observations presented here can constrain these predictions especially for the case of the Abell 85 cluster. © 2009 ESO.
Keywords: Galaxies: clusters: individual: Abell 496; Galaxies: clusters: individual: Abell 85; Gamma rays: observations

Very high energy γ-ray observations of the binary PSR B1259-63/SS2883 around the 2007 Periastron - van Eldik, Christopher; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, J.; et al. (Astronomy & Astrophysics, 2009)
Aims. This article presents very-high-energy (VHE; E > 100 GeV) data from the-ray binary PSRB1259-63 as taken during the years 2005, 2006 and before as well as shortly after the 2007 periastron passage. These data extend the knowledge of the lightcurve of this object to all phases of the 3.4 year binary orbit. The lightcurve constrains physical mechanisms present in this TeV source. Methods. Observations of VHE-rays with the HESS telescope array using the Imaging Atmospheric Cherenkov Technique were performed. The HESS instrument features an angular resolution of <0.1° and an energy resolution of <20%. Gamma-ray events in an energy range of 0.5-70 TeV were recorded. From these data, energy spectra and lightcurve with a monthly time sampling were extracted. Results. VHE-ray emission from PSRB1259-63 was detected with an overall significance of 9.5 standard deviations using 55 h of exposure, obtained from April to August 2007. The monthly flux of-rays during the observation period was measured, yielding VHE lightcurve data for the early pre-periastron phase of the system for the first time. No spectral variability was found on timescales of months. The spectrum is described by a power law with a photon index of G = 2.8 ± 0.2stat ± 0.2sys and flux normalisation F0 = (1.1 ± 0.1stat ± 0.2sys) × 10-12 TeV-1 cm-2 s-1. PSRB1259-63 was also monitored in 2005 and 2006, far from periastron passage, comprising 8.9 h and 7.5 h of exposure, respectively. No significant excess of-rays is seen in those observations. Conclusions.PSRB1259-63 has been re-confirmed as a variable TeV-ray emitter. The firm detection of VHE photons emitted at a true anomaly ? ≈-0.35 of the pulsar orbit, i.e. already 50 days prior to the periastron passage, disfavors the stellar disc target scenario as a primary emission mechanism, based on current knowledge about the companion star's disc inclination, extension, and density profile. © 2009 ESO.
Keywords: radiation mechanisms: non-thermal; methods: observational; stars: binaries: general; stars: neutron; gamma rays: observations; telescopes

VHE γ-ray emission of PKS2155-304: Spectral and temporal variability - van Eldik, Christopher; Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2010)
Context. Observations of very high-energy γ-rays from blazars provide information about acceleration mechanisms occurring in their innermost regions. Studies of variability in these objects lead to a better understanding of the mechanisms in play. Aims. To investigate the spectral and temporal variability of VHE (>100 GeV) γ-rays of the well-known high-frequency-peaked BL Lac object PKS 2155-304 with the HESS imaging atmospheric Cherenkov telescopes over a wide range of flux states. Methods. Data collected from 2005 to 2007 were analyzed. Spectra were derived on time scales ranging from 3 years to 4 min. Light curve variability was studied through doubling timescales and structure functions and compared with red noise process simulations. Results. The source was found to be in a low state from 2005 to 2007, except for a set of exceptional flares that occurred in July 2006. The quiescent state of the source is characterized by an associated mean flux level of (4.32 ± 0.09 ± 0.86) × 10 cm s above 200 GeV, or approximately 15% of the Crab Nebula, and a power-law photon index of Γ = 3.53 ± 0.06 ± 0.10. During the flares of July 2006, doubling timescales of ∼2 min are found. The spectral index variation is examined over two orders of magnitude in flux, yielding different behavior at low and high fluxes, which is a new phenomenon in VHE γ-ray emitting blazars. The variability amplitude characterized by the fractional rms F is strongly energy-dependent and is E. The light curve rms correlates with the flux. This is the signature of a multiplicative process that can be accounted for as a red noise with a Fourier index of ∼2. Conclusions. This unique data set shows evidence of a low-level γ-ray emission state from PKS 2155-304 that possibly has a different origin than the outbursts. The discovery of the light curve lognormal behavior might be an indicator of the origin of aperiodic variability in blazars. © ESO, 2010.
Keywords: BL Lacertae objects: individual: PKS 2155-304; galaxies: active; galaxies: jets; gamma rays: general